Access to dental public services by disabled persons - Leal Rocha, Lyana; Vieira de Lima Saintrain, Maria; Pimentel Gomes Fernandes Vieira-Meyer, Anya (BMC oral health, 2015)
Background According to the World Health Organization, one in every 10 people has a disability, and more than two-thirds of them do not receive any type of oral dental care. The Brazilian Constitution of 1988 guarantees all civilians including disabled people the right to healthcare, shaping the guidelines of the Brazilian National Health Care System ( Sistema Único de Saúde – SUS). However, there is limited information about the true accessibility of dental services. This study evaluated the accessibility of public dental services to persons with disabilities in Fortaleza, Ceará, which has the third highest disability rate in Brazil. Methods A cross-sectional quantitative study using structured questionnaires was administered to dentists (n = 89) and people with disabilities (n = 204) to evaluate the geographical, architectural, and organizational accessibility of health facilities, the communication between professionals and patients with disabilities, the demand for dental services, and factors influencing the use of dental services by people with motor, visual, and hearing impairments. Results 43.1% of people with disabilities do not recognize their service as a priority of Basic Health Units (BHU), 52.5% do not usually seek dental care, and of those who do (n = 97), 76.3% find it difficult to receive care and 84.5% only seek care on an emergency basis. Forty-five percent are unaware of the services offered in the BHU. Of the dentists, 56.2% reported difficulty in communicating with deaf patients, and 97.8% desired interpreters stationed in the BHU. People with disabilities gave better accessibility ratings than dentists (p = 0.001). 37.3% of the patients and 43.8% of dentists reported inadequate physical access infrastructure (including doors, hallways, waiting rooms, and offices). Dentists (60%) reported unsafe environments and transportation difficulties as geographical barriers, while most people with disabilities did not report noticing these barriers. Conclusions While access to dental services has increased in Fortaleza, the lack of accessibility of health units and their surroundings does not promote the treatment of people with disabilities. Cultural, organizational, architectural, geographical, and communication barriers constrain the demand for and use of oral dental care services by this social segment.